KERJASAMA ANTARA DOSEN DAN MAHASISWA DALAM PROSES PEMBELAJARAN DARING - Miptah Parid; Indah Hari Utami (NIZHAMIYAH, 2021)
This article reviews the cooperation between lecturers and students in the online learning process. this research uses qualitative approach with reasech library type. Data analysis techniques used are referring to the concept of Milles and Hubermen, namely interactive models that classify data analysis in three langakah, namely data reduction, data presentation and conclusion drawing. This research aims to find out the cooperation between lecturers and students in online learning. The conclusions of this study are: cooperation conducted between lecturers and students on online learning includes: 1) Discussions through zoom and whatsapp groups. Zoom application is an application used as a medium to communicate remotely by combining video conferences, chats, and meetings online, while discussion activities on online learning using whatsapp application can be in the form of problem solving, creating content, creating a work, responding and answering between lecturers and students; 2) make scientific papers. Scientific writing is a work that contains and examines a particular problem by using scientific rules. The scientific paper of a scientifically composed work; and 3) hold webinars. Webinar is a seminar, presentation, teaching or workshop conducted online through internet media and can be attended by many people who are in different areas Keywords: Lecturers, Students, Online Learning